Evaluating China’s Health System Performance Towards Universal Health Coverage - Dou, Jiaqi (International Journal of Public Health and Medical Research, 2026)
Achieving universal health coverage (UHC) is one of the core goals of the Sustainable Development Goals (SDGs), which aim to ensure that all individuals have access to quality health care without facing financial hardship. As the largest developing country, China has made remarkable progress in achieving UHC through healthcare financing and government leadership. However, urban and rural areas in China still face challenges in terms of access to health care, quality, and resource allocation. This structured literature review of articles published between 2010 and 2025 was conducted through PubMed and Google Scholar, and a total of 31 studies related to UHC and health systems in China were included as evidence for analysis. Through this literature review, we found that China has achieved more than 95% population coverage in terms of UHC, significantly improving access to basic health services. However, China’s financial protection indicators, such as Catastrophic Health Expenditure (CHE), are still higher than those of comparable countries. There are significant differences in the distribution of health human resources, the quality of medical services, and the quality of facilities between urban and rural medical institutions in China.